Dworkin e Raz: uma análise comparada sobre o conceito de direito, a relação entre direito e moral, e a interpretação jurídica - Christina Vilaca Brina (2016)
This research aims to understand, according to a comparative method, three aspects of the theories of Joseph Raz and Ronald Dworkin: the concept of law, the relation between law and morality, and legal interpretation. These aspects together are fundamental for the correct comprehension and application of law, being important a deeper debate about the present issues. In this sense, the analysis performed makes possible the identification and distinction between these theories, always remarking the crucial changes that legal positivist and anti-positivist theories have undergone over the last years. Furthermore, this article presents the most important critical answers raised about both legal theories by some of the best legal theory scholars, trying to achieve a broader understanding about the three aspects debated here.